2006
DOI: 10.1002/ajp.20281
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin function is associated with behavioral response to a novel conspecific in marmosets

Abstract: The function of the central nervous system neurotransmitter serotonin (5-HT) contributes to individual differences in impulsive behavior in humans and nonhuman primates. We investigated the relationship between 5-HT function and behavioral responses to a novel social scenario in marmosets. In the first study, marmosets (n=10) were treated orally with fluoxetine HCl (FLX) or vehicle for two trial periods and exposed to a novel conspecific for a 20-min trial following each treatment. Levels of behavioral inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…Our data illustrate an exciting alternative to the notion that early experience leads to stable individual differences in peripheral 5-HTT function: regulation of 5-HTT was influenced by early experience at an early stage in development. Although we predicted that 5-HTT expression would be stable and 'trait-like' as are other measures of 5-HT function (blood 5-HT, Kinnally et al 2006;CSF 5-HIAA, Higley & Linnoila 1997; brain 5-HTT availability, Ichise et al 2006), we did not observe differences in gene expression in the initial blood sample based on genotype or rearing. Instead, we found that MR infants upregulated 5-HTT in response to a stressor, while NR infants did not.…”
Section: Discussioncontrasting
confidence: 66%
“…Our data illustrate an exciting alternative to the notion that early experience leads to stable individual differences in peripheral 5-HTT function: regulation of 5-HTT was influenced by early experience at an early stage in development. Although we predicted that 5-HTT expression would be stable and 'trait-like' as are other measures of 5-HT function (blood 5-HT, Kinnally et al 2006;CSF 5-HIAA, Higley & Linnoila 1997; brain 5-HTT availability, Ichise et al 2006), we did not observe differences in gene expression in the initial blood sample based on genotype or rearing. Instead, we found that MR infants upregulated 5-HTT in response to a stressor, while NR infants did not.…”
Section: Discussioncontrasting
confidence: 66%
“…WBS has been shown to be higher in adolescent boys with conduct disorder and increased aggression (Unis et al, 1997). In animal studies, WBS levels were higher in less impulsive marmosets as exhibited by more inhibition in response toward a stranger (Kinnally et al, 2006), as well as dominant male vervet monkeys (Raleigh et al, 1983). In the present study, WBS was not predictive of eventual social rank nor was it different between dominant and subordinate monkeys during social housing.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT system has been implicated in a variety of social behaviors such as grooming, approaching, feeding, as well as impulsive aggression and impulsivity (Kaplan et al, 2002; Miczek et al, 2002, 2004a,b; Pattij and Vanderschuren, 2008). To assess 5-HT activity, the present study examined whole blood 5-HT (WBS) levels (Kinnally et al, 2006; Unis et al, 1997), cerebrospinal fluid (CSF) levels of the 5-HT metabolite 5-hydroxyindoleacetic acid (5-HIAA; Higley et al, 1991, 1992, 1996a,b; Higley and Linnoila, 1997; Kaplan et al, 2002; Westergaard et al, 1999; Yodyingyuad et al, 1985) and measures of 5-HT transporter (SERT) availability using positron emission tomography (PET; Frankle et al, 2005) in brain areas rich in SERT-containing terminals. Each 5-HT marker was examined in all monkeys allowing for comparisons of all dependent variables in a repeated-measures experimental design.…”
Section: Introductionmentioning
confidence: 99%
“…In macaque monkeys, behaviors of approach and aggression, which determine dominance, were measured in a test of social challenge involving dyads in a cage (Bachevalier et al 2001;Hadland et al 2003) and with long-term testing of a social group by the focal animal sampling method (Fairbanks et al 2001;Kaplan et al 2002;Newman et al 2005). In common marmosets, prior studies examined the neurochemical underpinnings of affiliative and agonistic behavior (Kinnally et al 2006), anxiety-related behaviors during confrontation with conspecific strangers (Cilia and Piper 1997;Kinnally et al 2006), and the propensity for monogamy (Gerber and Schnell 2004). For integrated analysis of behavioral responses in a social challenge condition in common marmosets, encounter trials between two subjects unfamiliar with each other were conducted (Fig.…”
Section: Features Of Molecular Brain Mapping Underlying Personality Tmentioning
confidence: 99%